Shuffled Frog Leaping Algorithm (SFLA) for solving profit based unit commitment problem / Nurul Izzati Mohd Hanapiah - Mohd Hanapiah, Nurul Izzati (2016)
This thesis presents the Shuffled Frog Leaping Algorithm (SFLA) technique is used to solve the Profit Based Unit Commitment Problem (PBUCP). The main purpose for solving this problem is to boost the Generation Companies (GENCOs) profit. PBUC problem depends on the right demand constraint and allocates fixed and transitional costs to the scheduled hours. GENCOs will reconstruct the operation system by scheduling their generators with the purpose to maximize their profit and minimize the cost. The proposed SFLA method is tested on a test system with ten generator units for a period of 24 hours. The results show that SFLA method can provide the solution for PBUCP.